Development of Interactive Learning Media for Teaching Hijaiyah Letters Using Sign Language to Students with Hearing Impairments - Muhammad Okeh Hartono; Supriadi (Journal of Contemporary Islamic Education, 2026)
Learning hijaiyah letters for students with hearing impairments requires learning media that accommodate auditory limitations and strengthen visual-based learning. This study aims to develop interactive multimedia for learning sign-based hijaiyah letters and examine its validity, practicality, and effectiveness in improving the mastery of hijaiyah letters among students with hearing impairments at State Special Schools in West Sumatra Province. This study employed a Research and Development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects involved expert validators, Islamic Religious Education teachers as practitioners, and students with hearing impairments in experimental and control classes. The instruments included validation sheets, practicality questionnaires, and pretest-posttest achievement tests. Validity data were analyzed using Aiken’s V index, practicality data using Moment Kappa, and effectiveness data using normality, homogeneity, paired sample t-test, and independent sample t-test. The results showed that the developed interactive multimedia obtained Aiken’s V scores of 1.00 for content, 1.00 for language, and 0.87 for construct. The practicality test obtained a Moment Kappa score of 0.98, categorized as very high. The average score of the experimental class increased from 52.27 to 86.13, while the control class increased from 45.09 to 64.36. The independent sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the two classes. Therefore, the developed interactive multimedia is valid, practical, and effective as an alternative learning medium for Islamic Religious Education for students with hearing impairments.